Unveiling The Lived Experiences of School Heads in Managing Intergenerational Diversity among Proficient Teachers - Lazaro, Bryan Louis G.; de Castro, Luningning B.; Henson, Luzale D.; Cainglet, Ronnie G.; del Rosario, Ligaya Z.; Buhain, Vivian I.; Tiratira, Niclie L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This transcendental phenomenological study explored the lived experiences of school heads in managing intergenerational diversity among proficient teachers in public elementary schools in Noveleta, Cavite. Through in-depth interviews, participant observations, and document analysis, the study revealed how generational differences impacted school management practices. Seven key themes emerged: Intergenerational Dynamics and Work Culture, Leadership and Adaptive Management Strategies, Technological Evolution and Pedagogical Adaptation, Communication, Collaboration, and Team Cohesion, Coping with Change and Navigating Resistance, Personal Well-being and Professional Growth, and Cultural and Societal Influences. The findings highlighted that school heads faced distinct challenges when managing generational gaps in work ethics, discipline, and professional values. Older generations of teachers, such as Baby Boomers and Generation X, exhibited stronger work ethics and commitment, often working through breaks to ensure student learning. In contrast, younger generations, particularly Generation Y and Z, were perceived to prioritize work-life balance and demonstrated less initiative. These differences posed significant challenges in fostering collaboration and innovation within schools. School heads employed adaptive strategies, such as empathetic leadership, fostering open communication, and promoting flexible solutions to bridge these generational divides. Moreover, the study emphasized the need for school management to address stereotypes and biases associated with different generations, creating inclusive environments that promoted cohesion and mutual respect. The implications extended to educational policies and professional development programs aimed at fostering intergenerational understanding and improving staff relations.